A CoMnSi-based magnetostrictive composite material and preparation method thereof

By simulating the rotating magnetic field curing orientation, a dense <100> preferential orientation CoMnSi-based/epoxy resin composite was prepared, which solved the problems of brittleness and large magnetic phase change critical field of the CoMnSi-based magnetostrictive material in practical applications, and achieved high-performance magnetostrictive effect.

CN117316564BActive Publication Date: 2025-04-04NANJING UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311245902.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-04
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

In practical applications, CoMnSi-based magnetostrictive materials face problems such as high brittleness, poor mechanical processing, large critical field of magnetic phase change, and small room temperature magnetostrictive performance. The existing improvement methods have not yet taken into account the improvement of magnetostrictive performance and mechanical performance.

Method used

The b-c crystal plane of the CoMnSi-based alloy in the antiferromagnetic state was used as the easy magnetization plane, and a method to simulate the curing orientation of the rotating magnetic field was designed to prepare a dense <100> preferential orientation of the CoMnSi-based/epoxy resin composite material.

Benefits of technology

It has achieved the characteristics of simple synthesis pathway, low production cost, low driving magnetic field and high orientation, which has significantly improved the magnetostrictive performance and mechanical properties of CoMnSi-based materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117316564B_ABST
    Figure CN117316564B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide a CoMnSi-based magnetostrictive composite material and a preparation method thereof, which specifically comprises the following steps: 1) preparing 30-300 micron CoMnSi-based alloy particles; 2) uniformly mixing the CoMnSi-based alloy particles with epoxy resin and placing them in a mold; 3) removing bubbles in the mixture using a vacuum pump; 4) orienting and curing the mold containing the mixture on a rotating table in a uniform magnetic field; 5) removing the CoMnSi-based and gold particle / epoxy resin composite material from the mold. The CoMnSi-based alloy molecular formula of the present invention is Co 1‑x Ni x MnSi (0.01≤x≤0.12), the epoxy resin includes epoxy resins such as E51 and E44 and a curing agent. This invention has been funded by the National Key R&D Program of "Frontier Research on Large Scientific Facilities" (2022YFA1602700).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional materials, and in particular relates to a CoMnSi-based magnetostrictive composite material and a preparation method thereof. Background Art

[0002] Magnetostrictive materials have many excellent physical properties such as high energy density, high energy conversion efficiency, and simple driving mode. They are widely used in shock absorption and shock protection, marine and offshore engineering, automation technology, micro-displacement driving and other fields. Textured Terfenol-D alloy (Tb x Dy (1-x) Fe2, 0.27≤x≤0.35) is the most famous magnetostrictive material at present, which can achieve a giant magnetostrictive effect of 1200 ppm under a 1 T magnetic field. However, the raw materials of Terfenol-D alloy contain expensive and easily oxidized heavy rare earth elements: Tb and Dy, which makes the alloy itself face defects such as high cost, scarce raw materials, large intrinsic brittleness, and strict preparation process. At present, there is still an urgent need for a cheap, high-performance magnetostrictive material on the market.

[0003] In recent years, CoMnSi-based alloys have attracted attention as a potential magnetostrictive material. Below the Néel temperature of CoMnSi alloys, the alloy undergoes a magnetic structure transition from a helical antiferromagnetic state to a ferromagnetic state (AFM-FM) induced by a magnetic field. This magnetic phase transition is accompanied by a severe anisotropic lattice distortion, which makes CoMnSi a potential magnetostrictive material. In 2010, Barcza et al. observed that at 280K, Co 0.95 Ni 0.05 During the magnetic phase transition of small particles of MnSi alloy oriented along the a-axis, the magnetostrictive effect reaches about -1200 ppm, which is comparable to some rare earth alloys. Compared with rare earth giant magnetostrictive materials, CoMnSi-based alloys have the following advantages as magnetostrictive materials: (1) the alloy raw materials are cheap and easy to obtain; (2) the preparation process requirements are relatively simple; (3) the magnetostrictive performance is excellent, which can theoretically reach 6000 ppm. The above factors have greatly improved the practical value of CoMnSi.

[0004] As magnetostrictive materials, CoMnSi-based alloys still face many difficulties in practical application: (1) CoMnSi bulk materials are brittle and have poor machinability; (2) The critical field of the magnetic phase transition of CoMnSi is very large, about 2.5 T at room temperature; (3) The magnetostrictive performance of CoMnSi polycrystalline bulk materials is small, and the linear magnetostrictive effect is only about 670 ppm. Therefore, people have tried to improve the magnetostrictive properties of CoMnSi-based alloys from three directions: improving mechanical properties; reducing the phase transition driving magnetic field; and preparing oriented textured CoMnSi-based alloy quick materials or composite materials. At present, there are three methods to improve mechanical properties: slow cooling process, resin filling process, and alloy / resin composite materials. Gong Yuanyuan, Hu Qiubo and others used the process of strong magnetic field directional solidification and slow cooling to prepare dense <111> Oriented CoMnSi 1-x (x = 0, 0.1, 0.2) bulk and densely textured CoMn 0.88 Si bulk material. Zhang Chengliang et al. used epoxy resin to fill the cracks of CoMnSi alloy to prepare CoMnSi bulk material with excellent mechanical properties. The main way to reduce the driving field of CoMnSi phase transition is the vacancy or doping of chemical elements. Gong Yuanyuan and Hu Qiubo introduced Si atom vacancies and Mn atom vacancies into CoMnSi alloy respectively. 0.88 The critical field of magnetic phase transition of Si alloy is reduced to about 1 T. Zhang Chengliang et al. used Ni to replace Co and Ge to replace Si in CoMnSi alloy; Gong Yuanyuan et al. used B to replace Si in CoMnSi alloy; Morrison et al. used Fe and Ni to replace Mn in the alloy, which reduced the driving field of magnetic phase transition of CoMnSi alloy.

[0005] CoMnSi-based alloy / epoxy resin composites are another way to prepare oriented and dense CoMnSi bulk materials. Neutron diffraction data show that the phase transition of the CoMnSi magnetic structure is accompanied by anisotropic lattice distortion: the changes in lattice constants a, b, and c are approximately -6000, 850, and 2000 ppm, respectively. This also shows that a-axis oriented or textured CoMnSi alloys or composites are likely to have higher magnetostrictive properties than other oriented or textured CoMnSi materials. Therefore, <100> Preferential orientation and reducing the driving magnetic field of CoMnSi magnetic phase transition are the two keys to improving the magnetostrictive properties of CoMnSi. Currently, there is no CoMnSi-based composite material that takes both properties into account. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a CoMnSi-based magnetostrictive composite material and a preparation method thereof. The method is based on the magnetic structure of CoMnSi, utilizes the fact that the bc crystal plane is an easy magnetization plane when the CoMnSi-based alloy is in an antiferromagnetic state, designs a method of simulating the solidification orientation of a rotating magnetic field, and prepares a dense <100> CoMnSi-based / epoxy resin composite material with preferred crystal orientation. The preparation method has the characteristics of simple synthesis route, low production cost, low driving magnetic field, high orientation degree, etc.

[0007] In order to achieve the above object, the present invention provides the following scheme:

[0008] A CoMnSi-based magnetostrictive composite material and a preparation method thereof, characterized in that the composite material is a CoMnSi-based alloy / epoxy resin composite material, the molecular formula of the CoMnSi-based alloy is Co 1-x Ni x MnSi (0.01≤x≤0.12, preferably x=0.05), epoxy resin refers to a polymer containing two or more epoxy groups in the molecule. It includes the following steps:

[0009] a. Preparation of Co 1-x Ni x MnSi (0.01≤x≤0.12) alloy particles;

[0010] b. uniformly mixing the CoMnSi-based alloy particles obtained in step a with epoxy resin in an appropriate proportion and placing the mixture in a mold;

[0011] c. placing the mold obtained in step b in a closed container, using a mechanical pump to slowly extract the air pressure in the container and maintain negative pressure for a period of time to remove pores in the composite material;

[0012] d. Take out the mold obtained in step c and place it on a rotating table, place the rotating table in a uniform magnetic field, make the rotating table surface parallel to the horizontal plane, turn on the rotating table, and make the mold obtained in step c rotate at a uniform speed in the horizontal direction and solidify in the uniform magnetic field;

[0013] e. Take out the mold in step d from the magnetic field, and take out the CoMnSi-based / epoxy resin composite material from the mold.

[0014] Furthermore, in step a, the CoMnSi-based alloy particles are particles having a chemical composition of Co 1-x Ni x The MnSi (0.01≤x≤0.12) alloy particles have a particle size of 20-300 microns, preferably a particle size of 30-100 microns, and can be prepared by crushing alloy ingots, commercial purchase, and the like.

[0015] Furthermore, in step b, the appropriate ratio is calculated based on the content of CoMnSi-based alloy particles in the CoMnSi-based / epoxy resin composite material, and the volume fraction of the particles is 10%-70%. The mixing step is to mechanically mix the metal particles with the solid dispersant or stir and uniformly mix them in a liquid (water, ethanol, etc.), or to achieve uniform mixing by dispersant-assisted dispersion.

[0016] Furthermore, in step c, the mechanical pump slowly draws out air pressure that is sufficient to slowly release bubbles from the epoxy resin, and the negative pressure is generally maintained for 1-5 minutes.

[0017] Furthermore, in step d, the frequency of the uniform rotation of the rotating table is 0.1-10 rpm, preferably 1-2 rpm. The intensity of the uniform magnetic field needs to be determined according to the magnetic properties of the CoMnSi-based alloy, generally 0.1-0.6 T, preferably 0.1-0.3 T.

[0018] The present invention discloses the following technical effects:

[0019] 1. The beneficial effects of the present invention are:

[0020] The present invention discloses a CoMnSi-based magnetostrictive composite material and a preparation method thereof, comprising Co 1-x Ni x It is composed of MnSi (0.01≤x≤0.12) alloy particles and epoxy resin, and has the characteristics of simple synthesis route, low production cost, low driving magnetic field and high orientation degree;

[0021] The preparation process of the present invention utilizes the magnetic property of the CoMnSi-based alloy with an easily magnetized surface, and uses a rotating magnetic field orientation method to prepare a characteristic <100> Preferentially oriented CoMnSi-based alloy / epoxy resin composite material. In addition, the present invention uses Ni atoms to replace the occupancy of Co atoms, which significantly reduces the driving magnetic field of the CoMnSi / epoxy resin composite material and promotes the application progress of CoMnSi-based materials in magnetostriction. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is to detect Co in Example 1 0.95 Ni 0.05 Magnetization curve of MnSi particles.

[0023] Figure 2 It is to detect Co before orientation in Example 1 0.95 Ni 0.05 MnSi particles and oriented Co 0.95 Ni 0.05X-ray diffraction pattern of MnSi / epoxy resin composites.

[0024] Figure 3 It is to detect Co near room temperature in Example 1 0.95 Ni 0.05 Magnetostriction curves of MnSi composites.

[0025] Figure 4 It is to detect Co before orientation in Example 2 0.95 Ni 0.05 MnSi particles and oriented Co 0.95 Ni 0.05 X-ray diffraction patterns of MnSi composites.

[0026] Figure 5 It is to detect Co in Example 3 0.97 Ni 0.03 Magnetization curves of MnSi / epoxy composites. DETAILED DESCRIPTION

[0027] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0028] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0029] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. Example 1

[0030] a. Obtaining Co by smelting method 0.95 Ni 0.05 MnSi intermetallic compound (subscript is atomic percentage), mechanically crushed to obtain powder with an average size of about 30μm to 100μm;

[0031] b. The CoMnSi-based alloy particles obtained in step a are uniformly mixed with epoxy resin (E51 and T31) in a volume ratio of 3:2 and placed in a mold;

[0032] c. Place the mold obtained in step b in a sealed container, use a mechanical pump to slowly extract the air pressure in the container and maintain negative pressure for 2 minutes to remove pores in the composite material;

[0033] d. Take out the mold obtained in step c and place it on a rotating table, place the rotating table in a uniform magnetic field of 0.2 T, make the rotating table surface parallel to the horizontal plane, turn on the rotating table, and make the mold obtained in step c rotate at a uniform speed in the horizontal direction and solidify in the uniform magnetic field for 24 h;

[0034] e. Take out the mold in step d from the magnetic field, and take out the CoMnSi-based / epoxy resin composite material from the mold.

[0035] Figure 1 is Co obtained in step a 0.95 Ni 0.05 The magnetization curve of MnSi particles shows that the critical field of magnetic phase transition of the particles is about 0.7 T and the saturation field is about 1.9 T. Figure 2 Is the orientation before Co 0.95 Ni 0.05 MnSi particles and oriented Co 0.95 Ni 0.05 X-ray diffraction pattern of MnSi / epoxy resin composites. After orientation, the composites show obvious <200> , <400> Preferred orientation of crystal direction. Figure 3 Co is near room temperature 0.95 Ni 0.05 Magnetostriction curves of MnSi composite materials. At 290K, Co 0.95 Ni 0.05 The magnetostriction of the MnSi composite material in the normal direction of the rotation plane reaches saturation near 2 T, which is about -1200 ppm. Example 2

[0036] a. Obtaining Co by smelting method 0.95 Ni 0.05 MnSi intermetallic compound (subscript is atomic percentage), mechanically crushed to obtain powder with an average size of about 30μm to 100μm;

[0037] b. The CoMnSi-based alloy particles obtained in step a are uniformly mixed with epoxy resin (E51 and T31) in a volume ratio of 3:2 and placed in a mold;

[0038] c. Place the mold obtained in step b in a sealed container, use a mechanical pump to slowly extract the air pressure in the container and maintain negative pressure for 2 minutes to remove pores in the composite material;

[0039] d. Take out the mold obtained in step c and place it in a uniform magnetic field of 0.2 T for curing for 24 h;

[0040] e. Take out the mold in step d from the magnetic field, and take out the CoMnSi-based / epoxy resin composite material from the mold.

[0041] Figure 4 For the orientation Co 0.95 Ni 0.05 MnSi particles and oriented Co 0.95 Ni 0.05 X-ray diffraction pattern of MnSi composite material. After orientation, Co 0.95 Ni 0.05 MnSi composites <013> , <020> , <004> The crystal orientation has been significantly enhanced. Example 3

[0042] a. Obtaining Co by smelting method 0.97 Ni 0.03 MnSi intermetallic compound (subscript is atomic percentage), mechanically crushed to obtain powder with an average size of about 30μm to 100μm;

[0043] b. The CoMnSi-based alloy particles obtained in step a are uniformly mixed with epoxy resin (E51 and T31) in a volume ratio of 3:2 and placed in a mold;

[0044] c. Place the mold obtained in step b in a closed container, use a mechanical pump to slowly extract the air pressure in the container and maintain negative pressure for 2 minutes to remove pores in the composite material;

[0045] d. Take out the mold obtained in step c and place it on a rotating table, place the rotating table in a uniform magnetic field of 0.2 T, make the rotating table surface parallel to the horizontal plane, turn on the rotating table, and make the mold obtained in step c rotate at a uniform speed in the horizontal direction and solidify in the uniform magnetic field for 24 h;

[0046] e. Take out the mold in step d from the magnetic field, and take out the CoMnSi-based / epoxy resin composite material from the mold.

[0047] Figure 5 is the Co obtained in step g 0.97 Ni 0.03 Magnetization curve of MnSi / epoxy composite material. The magnetization curve shows an obvious magnetic structure transition, with a critical field of magnetic phase transition of about 1.3 T and a saturation field of about 2.4 T. After Ni replaces Co, the critical field of magnetic phase transition is much lower than that of positive CoMnSi alloy (about 2.5 T).

[0048] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. The present invention will not be limited to the embodiments shown herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a CoMnSi-based magnetostrictive composite material, characterized in that: The following steps are involved: a. Preparation of Co 1-x Ni x MnSi alloy particles, wherein 0.01≤x≤0.12; b. uniformly mixing the CoMnSi-based alloy particles obtained in step a with epoxy resin in an appropriate proportion and placing the mixture in a mold; c. placing the mold obtained in step b in a closed container, using a mechanical pump to slowly extract the air pressure in the container and maintain negative pressure for a period of time to remove pores in the composite material; d. Take out the mold obtained in step c and place it on a rotating table, place the rotating table in a uniform magnetic field, make the rotating table surface parallel to the horizontal plane, turn on the rotating table, and make the mold obtained in step c rotate at a uniform speed in the horizontal direction and solidify in the uniform magnetic field for 24 hours to form; The frequency of the uniform rotation of the rotating table is 1-2 revolutions per minute; the field strength of the uniform magnetic field is 0.1-0.3 T; e. Take out the mold in step d from the magnetic field, and take out the CoMnSi-based / epoxy resin composite material from the mold.

2. The method for preparing a CoMnSi-based magnetostrictive composite material according to claim 1, characterized in that: In step a, the Co 1-x Ni x The MnSi alloy particles, with a particle size of 30-100 microns, are obtained by crushing alloy ingots and commercially purchasing methods.

3. The method for preparing a CoMnSi-based magnetostrictive composite material according to claim 1, characterized in that: In step b, the appropriate ratio is calculated based on the content of CoMnSi-based alloy particles in the CoMnSi-based / epoxy resin composite material, and the volume fraction of the particles is 10%-70%; the mixing step is to mechanically mix the alloy particles with the solid dispersant or stir them in a liquid to evenly mix them, or to achieve even mixing by dispersant-assisted dispersion; wherein the liquid is water or ethanol.

4. The method for preparing a CoMnSi-based magnetostrictive composite material according to claim 1, characterized in that: In step c, the mechanical pump slowly draws out air pressure that is sufficient to slowly release bubbles from the epoxy resin, and the negative pressure is generally maintained for 1-5 minutes.

Citation Information

Patent Citations

  • High-density giant magnetostrictive composite material forming device and method

    CN108682735A

  • Room-temperature magnetostrictive material and preparation method thereof

    CN110343931A